(untitled) (International Journal of Pathology and Genetics of Disease and Nursing Management, 2026)
Nurse educators occupy a pivotal position in strengthening healthcare systems by preparing competent nursing professionals capable of meeting contemporary healthcare demands. Rapid technological advancements, evolving disease patterns, globalization, and changing educational paradigms have transformed nursing education worldwide. Modern nurse educators are expected to integrate teaching, clinical practice, research, leadership, and innovation into educational frameworks that foster evidence-based practice and lifelong learning. However, challenges such as faculty shortages, technological adaptation, increased student diversity, and the widening gap between academic preparation and clinical realities necessitate strategic empowerment of nurse educators. This review explores the multifaceted role of nurse educators in bridging education, practice, research, and innovation. It highlights current challenges, technological advancements, research integration, innovative pedagogical approaches, leadership roles, and future perspectives that can strengthen nursing education globally. Empowering nurse educators through continuous professional development, institutional support, interprofessional collaboration, and digital transformation is essential for developing a resilient nursing workforce capable of addressing future healthcare challenges.